Relatedness of White-Tailed Deer from Culling Efforts Within Chronic Wasting Disease Management Zones in Minnesota - Alberto Fameli; Christopher Jennelle; Jessie Edson; Erik Hildebrand; Michelle Carstensen; W. David Walter (Pathogens)
In white-tailed deer (Odocoileus virginianus), closely related females form social groups, avoiding other social groups. Consequently, females infected with chronic wasting disease (CWD) are more likely to infect social group members. Culling has been used to reduce CWD transmission in high-risk areas; however, its effectiveness in removing related individuals has not been assessed. We analyzed 11 microsatellites and a mitochondrial DNA fragment to assess: (1) the genetic structure in white-tailed deer in Minnesota, USA and (2) the effectiveness of localized culling to remove related deer. For (1), we genotyped deer culled in 2019 and 2021 in three CWD management zones, and deer collected in between zones. For (2), we only included culled deer, defining “culled groups” as deer obtained in the same township-range-section and year. We compared mean relatedness among deer from the same culled group (intra-group relatedness) and among deer from different culled groups (inter-group relatedness). We did not find evidence of genetic structure, suggesting that an outbreak in any of the management zones could naturally spread to the others. Culling removed deer that were on average more related than expected by chance (intra-group relatedness > inter-group relatedness), and most highly-related deer were culled in the same bait site.